Cross Cultural Translation through Nawal El Saadawi's Works - Al Baqqarah, Lina Ali Ahmed (2005)
A Master of Arts thesis in English/Arabic/English Translation and Interpreting by Lina Ali Ahmed Al Baqqarah, "Cross Cultural Translation through Nawal El Saadawi's Works." Spring 2005. Available are Both Soft and Hard Copies of the Thesis.